Epidemiological and Clinical Profile of Lung Cancer in Kirkuk: Relationship with Demography, Tumour Types and Risk Factors - Abdullah, Fatima Qais; Saleh, Ahmed Hamad (American Journal of Biology and Natural Sciences, 2025)
Introduction & Aim: Lung cancer is still a significant health problem globally and is among the most common causes of cancer-related deaths, mainly because it closely correlates with smoking, environmental pollution and occupational exposure. Thus, the objective of this study was to examine demographic features as well as relationships between clinical symptoms and histological tumor types in patients with a diary history of lung cancer reporting to Kirkuk city. Materials & Methods: In this research 87 patients with lung cancer and 80 healthy individuals were enrolled via Azadi Teaching Hospital and the Oncology Center in Kirkuk from September 2024 to June 2025. Information was collected by structured questionnaires, clinical records and histopathological reports. We excluded incomplete clinical data and unclear history of smoking. Results: There was significant relationship between age and lung cancer as the incidence of lung cancer (n=92; 34.3%) increased from 51–60 years group to above (P<0.0001). Most cases were males (85.06%)Hence, there was a severe male predominance. There was no difference in place of residence, although patients who were from urban areas predominated slightly. Smoking status showed a strong and significant correlation, as 70.11% were current smokers. The most common symptom was cough (52.87%), followed by hemoptysis and dyspnea. Squamous cell carcinoma was the most common type histologically (67.82%), with large cell carcinom having the lowest frequencey. Conclusions: The present work shows that lung cancer in Kirkuk is greatly associated with age, smoking and male sex dominated disease where squamous cell carcinoma was the most frequent type of tumor. These results also underscore the importance of tailored preventive strategies and early diagnosis in high-risk populations. Local surveillance needs to be strengthened to improve the outcome of lung cancer.